Saliva as a Diagnostic Tool in Orofacial Disorders - Saliva, HIV, orofacial disorders (Institute of Medico-legal Publications Pvt Ltd, 2020)
Saliva is formed by major exocrine organs, namely the parotid gland, “sub-mandibular” gland and “sublingualglands” and many minor “salivary glands.” Nature has bestowed saliva “The natural source” with manyfunctional capabilities that have a crucial value in maintaining the well being of mouth. Saliva plays a majorrole in the protection of oral tissues, food preparation, digestion, lubrication and speech.1 But one purposenot given by life is the utilization of saliva for investigative value, it is the human who has to explore thisprecious wonder fluid marvelously studded with clues about the human body in health and disease. Saliva asa diagnostic aid in orofacial disorders is the traditional monitoring tool for various diagnosis.2